Climate change and corrosion damage risks for reinforced concrete infrastructure in China. Issue 4 (2nd April 2016) - Peng, Lizhengli; Stewart, Mark G.
Abstract : A changing climate which leads to increases in atmospheric CO2 concentration, and changes in temperature and relative humidity (RH), especially in the longer term, will accelerate the deterioration processes and consequently decline the safety, serviceability and durability of reinforced concrete (RC) infrastructure. This paper presents an investigation of carbonation-induced deterioration in three typical Chinese cities (Kunming, Xiamen and Jinan) under a changing climate. The changing trends of atmospheric CO2, local temperature and RH of typical Chinese cities are projected based on the latest CO2 emission scenarios. The time-dependent analysis is based on Monte Carlo simulation, and includes the uncertainty of climate projections, deterioration processes, material properties, dimensions and accuracy of predictive models. Deterioration of RC structures is represented by the probabilities of reinforcement corrosion initiation and damage. It was found that the mean carbonation depths by 2100 may increase by up to 45% for RC structures in China due to a changing climate. It was also found that climate change can cause an additional 7–20% of carbonation-induced damage by 2100 for RC buildings in temperate or cold climate areas in China. The findings provide a basis for the development of climate adaptation strategies through the improved design of concrete structures.